Migrasi dari Windows Server ke Linux Server Studi Kasus: Server POLY050 - Basuki Winoto; Deni Wardani (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2005)
File, as an important aspect of personal computer usage, can be managed personally by the ownerhimself or centralized in file storage servers. File storage server in Windows network environment use a specificcommunication protocol called SMB. This protocol, instead of being used by Windows Server, can also used bya server application called Samba which runs on Linux. Therefore, file storage server migration from WindowsServer to Linux Server is possible.Keywords: File, Storage, Windows, Linux, Samba